Manajemen Kesehatan Lingkungan Pada Kelompok Pemindang Di Tempat Pemindangan Ikan (TPI) Kusamba - Pande Ayu Naya Kasih Permatananda; I Gede Suranaya Pandit; Ni Wayan Erly Sintya Dewi; Asri Lestarini (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Like as the fish processing industry in general, the traditional processing industry also has a significant environmental impact. This community service was aimed to provide counselling related to environmental health management to a group of “pemindang” at central “pemindangan” industry Kusamba. The material provided is in the form of the benefit and importance of personal hygiene and environmental sanitation in fish processing, especially pindang, demonstration and exercise of 7 steps of hand washing, socialization on the use of personal protective equipment (PPE) and eco enzyme based on orange peel waste, and provision in providing garbage containers to improve environmental sanitation in the area of “pemindangan”. The participants had high enthusiasm in following the activities and from 10 participants who took the posttest, all of participants received score > 70. This empowerment activities are expected to be able to increase the knowledge of the group of “pemindang” on the importance of environmental health for fish processing industry, including “pemindangan” industry.